A Revision of the Neotropical Orb-Weaving Spider Genus Scoloderus (Araneae: Araneidae) - M. Brian Traw (Psyche: A Journal of Entomology)
More than one-fourth of the spiders examined for this revision were collected since the neotropical genus Scoloderus was revised in 1976. Thirteen names have been proposed for what appear to be five valid species (Scoloderus cordatus, S. gibber, S. nigriceps, S. tuberculifer, and S. ackerlyi). These species are distinguished by the presence or absence of abdominal humps on the female, the shape of the median apophysis of the male palpus, and the shape of the scape of the female epigynum. Abdominal coloration and pattern are highly variable and unreliable for identification. One new species, Scoloderus ackerlyi, is described on the basis of a single, unique female from Belize.